DNA‐Nanocrystal Assemblies for Environmentally Responsive and Highly Efficient Energy Harvesting and Storage - Mallikarjuna Reddy Kesama; Sunghwan Kim (Advanced Science)
Abstract Natural polymer‐based and self‐powered bioelectronic devices are attracting attention owing to an increased interest in human health monitoring and human–machine interfaces. However, obtaining both high efficiency and multifunctionality from a single natural polymer‐based bioelectronics platform is still challenging. Here, molybdenum disulfide (MoS2) nanoparticle‐ and carbon quantum dot (CQDs)‐incorporated deoxyribonucleic acid (DNA) nanocomposites are reported for energy harvesting, motion sensing, and charge storing. With nanomaterial‐based electrodes, the MoS2‐CQD‐DNA nanocomposite exhibits a high triboelectric open‐circuit voltage of 1.6 kV (average) and an output power density of 275 mW cm−2, which is sufficient for turning on hundred light‐emitting diodes and for a highly sensitive motion sensing. Notably, the triboelectric performance can be tuned by external stimuli (light and thermal energy). Thermal and photon energy absorptions by the nanocomposite generate additional charges, resulting in an enhanced triboelectric performance. The MoS2‐CQD‐DNA nanocomposite can also be applied as a capacitor material. Based on the obtained electronic properties, such as capacitances, dielectric constants, work functions, and bandgaps, it is possible that the charges generated by the MoS2‐CQD‐DNA triboelectric nanogenerator can be stored in the MoS2‐CQD‐DNA capacitor. A new way is presented here to expand the application area of self‐powered devices in wearable and implantable electronics.